Comparative effects of temperature and salinity on growth of four harmful Chattonella spp. (Raphidophyceae) from tropical Asian waters - Lum, Wai Mun; Sakamoto, Setsuko; Yuasa, Koki; Takahashi, Kazuya; Kuwata, Koyo; Kodama, Taketoshi; Katayama, Tomoyo; Leaw, Chui Pin; Lim, Po Teen; Takahashi, Kazutaka; Iwataki, Mitsunori (Frontiers in Marine Science, 2023)
In Asia, four harmful raphidophyte species, Chattonella malayana, C. marina, C. subsalsa, and C. tenuiplastida, coexist in the tropical waters but only C. marina was detected in temperate waters. This occurrence pattern pointed to a potentially distinct ecophysiological niche occupancy and possible species dispersion. The growth physiology of these species isolated from tropical Southeast Asia was investigated using unialgal cultures in ten temperatures (13.0–35.5°C) and five salinities (15–35) to better understand the factors driving their distribution. The highest maximum specific growth rates were observed in C. subsalsa (0.65 ± 0.01 d-1), followed by C. malayana (0.47 ± 0.03 d-1), C. marina (0.45 ± 0.02 d-1), and C. tenuiplastida (0.39 ± 0.01 d-1). Their optimal temperatures were 28.0, 30.5, 25.5, and 30.5°C, respectively, of which C. marina preferred colder water. C. subsalsa exhibited a wider growth temperature range (20.5–35.5°C), followed by C. marina (20.5–30.5°C), C. tenuiplastida (23.0–33.0°C), and C. malayana (25.5–33.0°C). Optimal salinities were similar between C. subsalsa and C. malayana (30), and between C. marina and C. tenuiplastida (25), but C. subsalsa and C. marina exhibited a similar growth salinity range of 15–35, while C. malayana and C. tenuiplastida was 20–35. High values of Fv/Fm were observed in C. subsalsa and C. marina (> 0.5) in all tested conditions, but Fv/Fm of C. malayana and C. tenuiplastida were significantly lower at 20.5°C. All four species achieved a maximum cell density of > 104 cells mL-1 in their optimal conditions. Optimal temperatures in C. subsalsa and C. marina were identical to previous reports. The high adaptability of C. subsalsa in various temperatures and salinities suggests its high competitiveness and bloom potential. The high adaptability of C. marina in colder waters compared to other species likely contributes to its wide distribution in the temperate Asian waters. The narrow temperature window of C. malayana and C. tenuiplastida suggests their endemicity and limited distribution in the tropical waters. This study provides evidence about the occurrences and bloom potential of Chattonella spp. in Asia, but the endemicity versus dispersion issue remains unresolved.